Menanamkan Kerjasama Pada Anak melalui Permainan Rangkuk Alu Di RA Azahra Cirebon - Siti Komariyah; Suzana Suzana; Neni Budiani (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah UI BBC, 2023)
The results of observations in Pen Pen Village found that children aged 5-6 years were more focused on playing with cellphones, did not socialize with their environment, the children's cooperative attitude was very low, and they were not interested in playing together with their peers. Apart from that, in the technologically advanced 4.0 era, traditional games are currently less popular. The aim of this research is to instill and develop an attitude of cooperation in children, as well as introduce traditional games as a cultural heritage that must be maintained. This research uses Classroom Action Research or PTK methodology, with a Kemmis and Taggart design. The results of the research show that there is development of social attitudes, cooperation, and interest in playing traditional games, so it can be concluded that the Rangkuk alu game can attract interest and instill cooperation in children at RA Al Zahra Cirebon.